Examination of the scientific research on the subject area of "Namaz" in Iranian and international databases - Hossein Batooli (Fiyz̤, 2020)
Background: Quantitative evaluation of scientific activities of "Namaz" help Policy makers to optimize the quality of planning in this area. Therefore, the purpose of this study was to measure the research output in the field of "Namaz". Materials and Methods: This is a descriptive survey which uses scientometrics approaches. The statistical population is the scientific production in the field of "Namaz", which will be indexed at SID, IDML, Scopus, WOS and Pubmed by the end of 2018. The year of publication, the author, the journal and the subject of these articles were reviewed. Results: Respectively 97 and 75 Persian and English articles were indexed in the field of ​​"Namaz". Malaysia and University of Malaya have the largest number of articles. The effectiveness of Namaz on mental and physical health, adherence to Namaz, tendency to Namaz, Namaz and art, secrets of Namaz, review of religious laws related to Namaz and the relationship of Namaz with other subjects such as lifestyle, politics, economic health, social health, ethical health, responsibility and quality of life are most important topics discussed in these articles. Conclusion: The results of this research indicate that the number of articles in the field of Namaz is low and there are no researchers and journals focused on this topic. Little research has been done on Namaz and the various aspects of social, moral, political, and economic health. Results can be applied with a holistic approach to different aspects of Namaz in order to design applied research plans in this regard.